Government Trade Promotion Agencies : Strategies for Enhancing Global Market Access - Vasylenko, Yelyzaveta (2024)
This thesis examines the role and key functions of GTPAs, their global best practices in trade promotion and their overall impact on economic growth. In addition, it is worth considering the main barriers these countries face when implementing trade agreements and GTPAs. Examine how these mechanisms impact the economic development of countries and what examples of successful application of these approaches can be identified.